Externalities in Urban Sustainability - Erik T. Verhoef; Peter Nijkamp (Tinbergen Institute, 2000)
This paper studies urban sustainability from the perspective ofexternalities. We develop a general spatialequilibrium model of a monocentric city, in which two types ofexternalities occur. On the one hand, pollution inthe industrial centre leads to a spatially differentiateddeterioration of the environmental quality in the residentialarea. On the other hand, the existence of the city is explained byagglomeration economies, represented as simpleMarshallian external benefits in production. We investigate free-market versus first-best and second-best optimalspatial equilibria, and conclude that the pursuit of environmentalgoals may sometimes come at the expense ofreduced agglomeration economies, but may actually sometimes alsostimulate these economies.
Keywords: D62; R13; R14; 330; Urban equilibrium; environmental externalities; agglomeration externalities; Externer Effekt; Räumliche Gleichgewichtstheorie; Nachhaltige Entwicklung; Agglomerationseffekt; Umweltbelastung; Stadt; Industrie; Theorie